Improving knowledge management and organisational learning: the use of scenarios and domain memory in academic tutoring. (7th July 2010) - Osatuyi, Babajide; Andoh-Baidoo, Francis Kofi; Blue, Jon
In this paper, we present an approach for sharing knowledge that utilises features of Domain Memory Information Systems to support academic tutoring. This approach uses Scenarios for capturing tacit knowledge and ontology for standardising data from diverse knowledge sources, as well as presenting a common understanding of concepts among the tutors and tutees. Using the Nonaka and Takeuchi's knowledge spiral model, we demonstrate how the architecture supports the knowledge management process from the acquisition of tacit knowledge through sharing of explicit knowledge among tutors and tutees.